A new record of a pest mite on strawberry: Phytonemus pallidus (Banks) (Acari: Tarsonemidae) Arrives in Minas Gerais, Brazil - Vacacela Ajila, Henry E.; Lemos, Felipe; Colares, Felipe; Ferreira, João A. M.; Lofego, Antônio C. [UNESP]; Pallini, Angelo (De Gruyter, 2018)
Summary Phytonemus pallidus was found in organic strawberry crops in 2 municipalities in the state of Minas Gerais. The sparse information about this pest in the country indicated that P. pallidus had been observed previously only on grapes in southern Brazil. The presence of this pest in the country is relatively new, although in the USA and in some European countries it is already well known due to the economic losses it causes. The report of the occurrence of this herbivore, as well as the affected crops, is essential for the official institutions to take appropriate measures to prevent dispersion to other states. Future studies should be directed to the search for effective alternatives for the management of this pest, because currently there are no insecticides registered for control in Brazil. An alternative that could be considered is biological control.
Keywords: cyclamen mite; first report; organic strawberry crops; phytophagous mite